A New Dibenzocyclooctadiene Lignan from Stems of Schisandra lancifolia and its Bioactivities - Li, Yin-Ke; Wu, Xian-Xue; Li, Ming; Du, Gang; Hu, Qiu-Fen; Gao, Xue-Mei (Asian Journal of Chemistry, 2013)
A new dibenzocyclooctadiene lignan, lanciphenol A (1) was isolated from the stems of Schisandra lancifolia. The structure of 1 was elucidated by spectroscopic methods including extensive 1D and 2D NMR techniques. Compound 1 was evaluated for its anti HIV activity and cytotoxicity. It showed anti HIV-1 activity with therapeutic index value of 64.8 and cytotoxicity against NB4, A549 and MCF7 cell with IC50 values of 6.8, 7.5 and 8.4 μM, respectively.